A number of institutional and legal issues concerning the management of digital data-based sources developed by applying the internet of things in Vietnam - Sinh, Bach Tan; Duong, Duong Khanh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
Facilitating the development of the Internet of Things (IoT) is an indispensable requirement in building a digital economy in which trust is the foundation of the IoT. The article shares some initial thoughts about institutional and legal issues related to management of digital data-based sources developed by the applying the IoT in Vietnam from international experience and current situation in Vietnam, from which proposing the legal and institutional frameworks related to ensuring the safety and protecting the individuality of the data collected from the IoT. Code: 21031101